2021
DOI: 10.1038/s41467-021-25653-w
|View full text |Cite
|
Sign up to set email alerts
|

Nrf1 promotes heart regeneration and repair by regulating proteostasis and redox balance

Abstract: Following injury, cells in regenerative tissues have the ability to regrow. The mechanisms whereby regenerating cells adapt to injury-induced stress conditions and activate the regenerative program remain to be defined. Here, using the mammalian neonatal heart regeneration model, we show that Nrf1, a stress-responsive transcription factor encoded by the Nuclear Factor Erythroid 2 Like 1 (Nfe2l1) gene, is activated in regenerating cardiomyocytes. Genetic deletion of Nrf1 prevented regenerating cardiomyocytes fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 60 publications
2
60
1
Order By: Relevance
“…55, 56 HMOX1 is an important activator of NRF1, which has been recently discovered to be involved in heart regeneration and repair, promoted by NRF1 signaling. 57 Importantly, four members of the family of glutathione peroxidases involved in the termination reaction of ROS pathways were increased in TG AC8 vs WT: Gpx3 (transcripts by 103%, proteins by 30%); Gpx7 (transcripts by 40%, proteins by 21%); Gpx8 (transcripts by 20%, proteins by 16%); Gpx1 (transcripts by 39%, proteins by 12%). Several members of glutathione transferases were differentially expressed in TG AC8 vs WT: Gsta3 (transcripts and proteins upregulated by 55% and 26% respectively); GSTM5 (proteins upregulated by 23%), GSTM1 (proteins upregulated by 14%); mitochondrial glutathione reductase GSR was also upregulated, while GSTM7 (transcripts and proteins were decreased by 21%, and 9%) and GSTO1 (protein was decreased by 9%).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…55, 56 HMOX1 is an important activator of NRF1, which has been recently discovered to be involved in heart regeneration and repair, promoted by NRF1 signaling. 57 Importantly, four members of the family of glutathione peroxidases involved in the termination reaction of ROS pathways were increased in TG AC8 vs WT: Gpx3 (transcripts by 103%, proteins by 30%); Gpx7 (transcripts by 40%, proteins by 21%); Gpx8 (transcripts by 20%, proteins by 16%); Gpx1 (transcripts by 39%, proteins by 12%). Several members of glutathione transferases were differentially expressed in TG AC8 vs WT: Gsta3 (transcripts and proteins upregulated by 55% and 26% respectively); GSTM5 (proteins upregulated by 23%), GSTM1 (proteins upregulated by 14%); mitochondrial glutathione reductase GSR was also upregulated, while GSTM7 (transcripts and proteins were decreased by 21%, and 9%) and GSTO1 (protein was decreased by 9%).…”
Section: Discussionmentioning
confidence: 94%
“…55,56 HMOX1 is an important activator of NRF1, which has been recently discovered to be involved in heart regeneration and repair, promoted by NRF1 signaling. 57 Importantly, four members of the family of glutathione peroxidases involved in the termination reaction of ROS pathways were increased in TG AC8 vs WT: Gpx3 (transcripts by 103%, proteins by 30%); Gpx7 (transcripts by 40%, proteins by 21%); Gpx8 (transcripts by 20%, proteins by 16%); Gpx1 (transcripts by 39%, proteins by 12%). Several members of glutathione transferases were differentially expressed in TG AC8 vs WT:…”
Section: Ros Regulationmentioning
confidence: 94%
“…In addition, SIRT1 can deacetylate PGC-1α, activating a suite of genes [50] involved in mitochondrial function and biogenesis, such as nuclear respiratory factor-1 (Nrf1) [49,53]. Consistent with this, a recent study showed that NRF1 could protect human-induced pluripotent stem cells (hiPSC)-derived cardiomyocytes against a range of cardiotoxins, including DOX [54]. In summary, sirtuins can regulate mitochondrial function and thereby promote cardiomyocyte survival.…”
Section: Dox Accumulates In the Mitochondria And Perturbs Mitochondri...mentioning
confidence: 74%
“…For example, scRNA-seq can confirm and enrich the regional gene expression data obtained by spRNA-seq to generate a 3D atlas of the human embryonic heart (Asp et al, 2019). Similarly, by combining scRNA-seq and spRNA-seq, one subpopulation of cardiomyocytes overexpressing Nrf1 has been identified near the infarcted region of the heart (Cui et al, 2021). Thus, the activation of the Nrf1 pathway represents a new therapeutic approach for cardiac injury.…”
Section: Scrna-seq and Bulk And Spatial Rna Sequencingmentioning
confidence: 99%